Echocardiographic Management of papillary muscle rupture during acute myocardial infarction - Paolo G. Pino; Iris Parrini; Antonella Moreo; Antonio Terranova; Federico Nardi (Exploration of Cardiology, 2025)
Papillary muscle rupture is a rare but fatal complication of acute myocardial infarction. The incidence of this complication has been reduced to less than 0.1% of patients due to the advent of primary percutaneous coronary intervention. Cardiogenic shock and acute pulmonary edema are the most common clinical presentations. In this review, we describe the role of transthoracic and transesophageal echocardiography in identifying the type, location, and hemodynamic consequences of the three different echocardiographic patterns of papillary muscle rupture. This information is crucial for managing medical therapy and determining the appropriate surgical or percutaneous treatment.